Energy efficient, clean and solvent free photochemical benzylic bromination using NBS in concentrated solar radiation (CSR). (March 2015) - Deshpande, Saurabh; Gadilohar, Balu; Shinde, Yogesh; Pinjari, Dipak; Pandit, Aniruddha; Shankarling, Ganapati
Graphical abstract: Highlights: First use of concentrated solar radiations for benzylic bromination using Fresnel lens. Energy efficient and green alternative for traditional methods of benzylic bromination. Good yield and less reaction time. Use of renewable energy source and solvent free reaction condition (SFRC). Abstract: An environmentally benign, clean, solvent free approach for the benzylic bromination have been developed using concentrated solar radiation (CSR). CSR methodology was used as an energy source to the reaction media. The protocol was found to be superior to the conventional photochemical and thermal methods in terms of reaction time and total energy requirement. This method was adapted with concentrated solar radiations in solvent free conditions without the use of radical initiators and has proved to provide good yields. Incorporation of renewable energy source, minimisation of raw materials makes the process not only green but energy efficient also.